Optimización del plan de mantenimiento usando la metodología de Mantenimiento centrado en confiabilidad viviente (L-RCM) para los equipos de la flota de tractores orugas de Carbones del Cerrejón Limited - Diaz, Henry Alberto (Universidad Antonio Nariño, 2021)
In this research, it is proposed to develop the methodology of Living Reliability Centered Maintenance (l-RCM), for the case study the maintenance of caterpillar equipment will be worked, specifically to the fleet of Tractors (D9T, D10T, D11T) of the Carbones del Cerrejón Limited company, in which there is low reliability and availability. The general objective is to Optimize the maintenance plan using the Reliability Centered Maintenance - Living (L-RCM) methodology. In relation to the methodology for the LRCM implementation process, it includes several phases, initially it is intended to update the RCM analyzes of the Tractor fleet, in the second instance documenting in the RCMCost software the RCM analyzes of the fleet, finally, the different systems, components and parts, functions, functional failures and causes defined in the RCM analyzes. It was determined in the criticality analysis of the CAT D9T Crawler Tractor we can note that the fuel subsystem, Arm cylinder and lubrication are the critical systems, likewise, for the CAT D10T Crawler Tractor we can note that the fuel subsystem, Pump Hydraulics and lubrication are critical systems. Finally, the CAT D9T Crawler Tractor we can note that the fuel, boom cylinder and lubrication subsystem are the critical systems. In the table we show the fault record according to the fuel filter hour meter